The association between aspects of daily life and quality of life of people with dementia living in long-term care facilities: a momentary assessment study. (12th April 2016) - Beerens, Hanneke C.; de Boer, Bram; Zwakhalen, Sandra M.G.; Tan, Frans E.S.; Ruwaard, Dirk; Hamers, Jan P.H.; Verbeek, Hilde
ABSTRACT: Background: To improve the quality of life (QoL) of people with dementia (PwD) living in long-term care facilities, insight into the association between QoL and how people spend their daily lives is urgently needed. This study investigated which aspects of daily life are related to QoL in dementia. Methods: An observational study was conducted. Daily life was assessed with the tablet-based Maastricht Electronic Daily Life Observation-tool (MEDLO-tool). Aspects included activity, engagement in the activity, social interaction, physical effort, mood, and agitation. QoL was assessed by formal nursing caregivers using the Quality of Life-Alzheimer's Disease scale (QoL-AD). A total of 9, 660 momentary assessments were conducted. Results: The mean age of the 115 participants was 84 years and most (75%) were women. Bivariate analyses showed that residents with a higher QoL carried out less passive/purposeless activities (25% vs. 38%), were more engaged in active, expressive, and social activities, (40% vs. 27%), had more social interaction (34% vs. 22%), and had better mood scores (scale 1–7, 5.0 vs. 4.8), compared with residents with a lower QoL (all p -values < 0.001). Multivariate analyses showed that having more social interaction and a positive mood are related to a higher QoL. Conclusions: The results underline the importance of social interaction and a positive mood for a higher QoL. Future research should investigate the importance of engagement in activities in more detail.